(untitled) (Global Journal of Medical Research, 2019)
Patient health records (both dental and medical), if accurately maintained not just help in better clinical decisions for the welfare of the patient but also have legal and other security benefits for the doctor. As digitization has paved its way in every stream, the same has occurred to maintaining of patient records, which when electronically controlled are termed as the Electronic patient records (EPR) or Electronic dental records (EDR) or Electronic medical records (EMR) pertaining to the dental details or the medical respectively. They would provide the advantages of well maintained paper records with benefits of cross-referencing the data by consulting specialists and help to integrate the medical and dental fraternity. The use of EDR is more widespread internationally in US and European countries compared to the developing ones. Many challenges do exist for a complete transition, including financial restraints, skill development, confidentiality of records and their standardization. In developing countries demographics makes it more difficult to apply the EDR but efforts are ongoing. This narrative review discusses the various systems of EDR, their benefits and functioning, and also the hindrances in path of their acceptance.